Stratum basale keratinocyte expression of the cell‐surface glycoprotein CDCP1 during epidermogenesis and its role in keratinocyte migration. (28th February 2013) - McGovern, J.A.; Heinemann, J.R.; Burke, L.J.; Dawson, R.; Parker, T.J.; Upton, Z.; Hooper, J.D.; Manton, K.J.
Summary Background Epidermogenesis and epidermal wound healing are tightly regulated processes during which keratinocytes must migrate, proliferate and differentiate. Cell‐to‐cell adhesion is crucial to the initiation and regulation of these processes. CUB‐domain‐containing protein (CDCP)1 is a transmembrane glycoprotein that is differentially tyrosine phosphorylated during changes in cell adhesion and survival signalling, and is expressed by keratinocytes in native human skin, as well as in primary cultures. Objectives To investigate the expression of CDCP1 during epidermogenesis and its role in keratinocyte migration. Methods We examined both human skin tissue and an in vitro three‐dimensional human skin equivalent model to examine the expression of CDCP1 during epidermogenesis. To examine the role of CDCP1 in keratinocyte migration we used a function‐blocking anti‐CDCP1 antibody and a real‐time Transwell™ cell migration assay. Results Immunohistochemical analysis indicated that in native human skin CDCP1 is expressed in the stratum basale and stratum spinosum. In contrast, during epidermogenesis in a three‐dimensional human skin equivalent model, CDCP1 was expressed only in the stratum basale, with localization restricted to the cell–cell membrane. No expression was detected in basal keratinocytes that were in contact with the basement membrane. Furthermore, an anti‐CDCP1 function‐blocking antibody was shown to disrupt keratinocyte chemotactic migration in vitro. Conclusions These findings delineate the expression of CDCP1 in human epidermal keratinocytes during epidermogenesis and demonstrate that CDCP1 is involved in keratinocyte migration.